2019
DOI: 10.1371/journal.pone.0227313
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between scapular initial position and scapular movement during dynamic motions

Abstract: Optimal scapular position and movement are necessary for normal function of the shoulder joint and it is essential to focus on scapula in the rehabilitation for shoulder disorders. The aim of this study was to discover the relationship between the scapular initial position and scapular movement during dynamic motions in healthy young men. Thirty-four men participated in this study. The scapular angles at initial position and in elevation and lowering during flexion and abduction were measured using an electrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…To ensure reproducible, physiological force transmission in the dynamic electrical testing machine (Instron E3000, Instron, Norwood, MA, USA), the specimens were clamped in an anatomically correct position with a negative mold made of polyurethane resin (RenCast FC52/53, Huntsman Advanced Materials, Basel, Switzerland). Due to the fact that the anatomical position of the scapula is dependent on arm movements, the scapula was positioned in the test machine with 15° of internal rotation, 13° of upward rotation, and 0° of anterior tilt to mimic the natural position of the scapula during 40° of arm abduction [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…To ensure reproducible, physiological force transmission in the dynamic electrical testing machine (Instron E3000, Instron, Norwood, MA, USA), the specimens were clamped in an anatomically correct position with a negative mold made of polyurethane resin (RenCast FC52/53, Huntsman Advanced Materials, Basel, Switzerland). Due to the fact that the anatomical position of the scapula is dependent on arm movements, the scapula was positioned in the test machine with 15° of internal rotation, 13° of upward rotation, and 0° of anterior tilt to mimic the natural position of the scapula during 40° of arm abduction [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Regarding outcomes, a significantly better shoulder motion of forward flexion and higher Constant score was observed in the improved SD group, and every patient with improved SD showed successful rotator cuff healing. Full overhead flexion or shoulder joint external rotation would be difficult without posterior tilting or external rotation of the scapula [34]. In this study, posterior tilting was most prominently enhanced in the improved SD group, which may explain why the forward flexion was significantly better in the improved SD group than in the sustained SD group.…”
Section: Discussionmentioning
confidence: 73%
“…Causes of abnormal non-paretic upper limb kinematics have been previously discussed [11] in terms of neurological impairment due to stroke consequences on neural pathways in the contralateral hemisphere and biomechanical improper function, so the non-paretic upper limb should not be considered for comparison with the affected limb. Normally, in healthy subjects, as measured via 3D kinematic evaluation [10,12,32], during shoulder flexion, the scapula shows upward rotation and external rotation followed by internal rotation and posterior tilt, and upward, external rotation, and posterior tilt during abduction. The findings in the present study confirm the reduced posterior tilt observed by other authors [8,12,33] during arm elevation.…”
Section: Discussionmentioning
confidence: 99%